2014
DOI: 10.1002/stem.1667
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Retinal Development with Patient-Specific Induced Pluripotent Stem Cells Reveals Multiple Roles for Visual System Homeobox 2

Abstract: Human induced pluripotent stem cells (hiPSCs) have been shown to differentiate along the retinal lineage in a manner that mimics normal mammalian development. Under certain culture conditions hiPSCs form optic vesicle-like structures (OVs), which contain proliferating progenitors capable of yielding all neural retina (NR) cell types over time. Such observations imply conserved roles for regulators of retinogenesis in hiPSC-derived cultures and the developing embryo. However, whether and to what extent this ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 54 publications
4
135
0
Order By: Relevance
“…Taking advantage of this multi-step protocol combining suspension and adherent cell cultures, Meyer et al confirmed the possibility of employing hES cells able to produce an enriched population of photoreceptor cells and RPE at the earliest stage of retinal specification that closely mimics the key developmental stages of retinogenesis. Later on, other papers published by the same group validated these results [59,60].…”
Section: The 3d Culture System Allows the Generation Of Bona Fide Phomentioning
confidence: 73%
See 1 more Smart Citation
“…Taking advantage of this multi-step protocol combining suspension and adherent cell cultures, Meyer et al confirmed the possibility of employing hES cells able to produce an enriched population of photoreceptor cells and RPE at the earliest stage of retinal specification that closely mimics the key developmental stages of retinogenesis. Later on, other papers published by the same group validated these results [59,60].…”
Section: The 3d Culture System Allows the Generation Of Bona Fide Phomentioning
confidence: 73%
“…Taking advantage of this multi-step protocol combining suspension and adherent cell cultures, Meyer et al confirmed the possibility of employing hES cells able to produce an enriched population of photoreceptor cells and RPE at the earliest stage of retinal specification that closely mimics the key developmental stages of retinogenesis. Later on, other papers published by the same group validated these results [59,60].In 2011, the first striking protocol using a 3D culture system during the whole experiment has been developed by the Sasai's group to differentiate mouse ES into optic cups forming well-structured retina tissues [61] (Figure 1). This masterwork has been briefly followed by a second one exclusively focused on human ES [62].…”
mentioning
confidence: 91%
“…Upon further differentiation, photoreceptor-like cells and RPE were derived from the vesicle-like structures. Similar optic vesicle-like structures have also been generated from lymphocyte-iPSC [4,36]. Zhong et al recently reported three-dimensional laminated retinal cups generated from human iPSC with distinct populations of neural retinal cells interacting through synaptic junctions and photoreceptor cells capable of forming outer segment discs and responding to light [57].…”
Section: Derivation Of Patient-specific Retinal Cells From Ipsc Fomentioning
confidence: 94%
“…These 3D functional organoids have improvised our understanding of early human development and improved drug screening methodologies organoids including mini gut, mini heart (repopulating decellularized mice heart through iPS), mini brain (developing cortex, central telencephalon and choroid plexus), small lungs, mini eyes (optic vesicle like structures) have been formulated for disease remodeling purposes [82][83][84][85][86][87][88][89].…”
Section: D Organoidsmentioning
confidence: 99%